Fluoroalkyl side group-containing acrylic resin for powder coating and preparation method of fluoroalkyl side group-containing acrylic resin

By using fluorine-containing alkyl pendant acrylic resin in powder coatings, the problem of insufficient light retention of existing powder coatings is solved, and higher water resistance and light retention are achieved, meeting customers' appearance needs.

CN119431656APending Publication Date: 2025-02-14ZHAOQING QIANJIANG WATER PAINT CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411649431.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing powder coatings lack the light retention after long-term use, which is difficult to meet customers' appearance needs.

Method used

A fluoroalkyl pendant acrylic resin is used to form a fluoroalkyl group by reacting ethyl trifluoroacrylate with propylene glycol methyl ether acetate, thereby enhancing the hydrophobicity and light retention of the resin.

Benefits of technology

It significantly improves the water resistance and light retention of powder coatings, so that the coating can still maintain a good appearance after long-term use, and enhances its practicality and wide application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431656A_ABST
    Figure CN119431656A_ABST
Patent Text Reader

Abstract

The invention provides fluoroalkyl side group-containing acrylic resin for a powder coating and a preparation method of the fluoroalkyl side group-containing acrylic resin, ethyl trifluoroacrylate (TFEA), glycidyl methacrylate (GMA) and methyl methacrylate (MMA) are added and mixed in a certain proportion range to obtain a mixed solution, so that the ethyl fluoroacrylate is subjected to a polymerization reaction, and the fluoroalkyl side group-containing acrylic resin is obtained. And heat preservation is arranged, so that a mixed solution can be fully reacted, then solute of the mixed solution can be separated out through vacuumizing, and finally, the transparent fluoroalkyl-containing side group acrylic resin with high water resistance and ageing resistance can be obtained through drying, and the water resistance and gloss retention are good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of powder coatings, and in particular to a fluorine-containing alkyl side group acrylic resin for powder coatings and a preparation method thereof. Background Art

[0002] With the advancement of environmental awareness, powder coatings have been widely favored for their significant advantages of being solvent-free and pollution-free. There are various types of powder coatings, which are used in various anti-corrosion and decorative places. Powder coatings can be roughly divided into two categories: thermosetting and thermoplastic according to their different curing mechanisms. Thermoplastic powder coatings do not undergo chemical reactions when forming films. The coating just melts and flows when it is heated and then solidifies into films when it is cooled. The processing process is relatively simple and mainly includes types such as polyethylene and polyvinyl chloride. Thermosetting powder coatings include resins and curing agents in their formulas. During the melting process, a curing and cross-linking reaction will occur between the resin and the curing agent to form a dense and stable three-dimensional network structure with more superior performance, occupying a dominant position in the powder coating market.

[0003] For example, Chinese patent application No. 202311858656.2, with a publication date of March 1, 2024, discloses a silicone resin for powder coatings, a preparation method and an application thereof, wherein the silicone resin for powder coatings has a structure as shown in the following formula A, wherein R and R' are methyl or phenyl, m=120-160, x=5-10, y=7-12 and m, x, y are integers. The silicone resin for powder coatings is prepared by the following steps: (1) reacting 2,3-dihydroxypropyl methacrylate with 2,2-bis(trifluoromethyl)propionyl fluoride to prepare a fluorine-containing monomer; (2) hydrosilylation of the fluorine-containing monomer with a low-hydrogen polysiloxane to prepare the silicone resin for powder coatings.

[0004] In the prior art, fluorinated monomers are grafted onto polysiloxane via silicone resins. Due to their unique structure, they have excellent high temperature resistance and salt spray resistance, and low surface tension. However, although polysiloxane grafted fluorinated monomers have high temperature resistance, they have gloss retention after long-term use. However, for coating products, they still maintain a certain gloss after long-term use, which can make the appearance more popular with customers. Summary of the invention

[0005] The purpose of the present invention is to provide a fluorinated alkyl side group acrylic resin for powder coatings and a preparation method thereof, which can effectively improve the water resistance and gloss retention of the powder coatings, has strong practicality, and makes the application more extensive.

[0006] To achieve the above object, the present invention provides a fluorinated alkyl side group acrylic resin for powder coatings, comprising the following preparation materials: Ethyl trifluoroacrylate (TFEA), glycidyl methacrylate (GMA), methyl methacrylate (MMA), di-tert-butyl peroxide (DTBP), propylene glycol methyl ether acetate (PMA); The weight ratio of ethyl trifluoroacrylate (TFEA): glycidyl methacrylate (GMA): methyl methacrylate (MMA) is in the range of 1~5:6~15:1~9; The weight ratio of ethyl trifluoroacrylate (TFEA): di-tert-butyl peroxide (DTBP): propylene glycol methyl ether acetate (PMA) is in the range of 1-5: 1.5-2.5: 30-50.

[0007] The above materials utilize the fluorine group of ethyl trifluoroacrylate, so that it reacts with propylene glycol methyl ether acetate to form a fluoroalkyl group, and the addition of the fluoroalkyl group significantly enhances the hydrophobicity of the resin, so that the subsequent coating has strong water resistance. In addition, methyl methacrylate has good coloring properties, so that after reacting with propylene glycol methyl ether acetate, the gloss retention is better. Glycidyl methacrylate, as an ester compound, provides a basis for forming the resin.

[0008] Another aspect of the present invention provides a method for preparing a fluorinated alkyl side group acrylic resin, comprising the following steps: S1: A stirrer, a constant pressure dropping funnel, a condenser and a thermometer are installed on the reactor; S2: adding propylene glycol methyl ether acetate (PMA) into the reactor, stirring the reactor with a stirrer, and heating the reactor to a polymerization temperature after stirring. S3: uniformly mixing ethyl trifluoroacrylate (TFEA), glycidyl methacrylate (GMA) and methyl methacrylate (MMA) in a weight ratio of 1-5:6-15:1-9, and then mixing with 90% of di-tert-butyl peroxide (DTBP) to obtain a mixed solution; S4: injecting the mixed solution in step S3 into a constant pressure dropping funnel, and then dripping it into the reactor at a uniform speed through the constant pressure dropping funnel. After the mixed solution is dripped, it is kept warm for a period of time T, and then the remaining 10% of di-tert-butyl peroxide (DTBP) in step S3 is added to the reactor, and the temperature is kept warm for a period of time T; S5 After the mixed solution has fully reacted, continue to heat and raise the temperature to a preset temperature, then stop heating and keep warm, and at the same time evacuate the reactor to maintain the vacuum degree in the reactor within a preset pressure range to remove the solvent, then put the precipitated material after the solvent is removed into a vacuum drying oven and dry for 8-10 hours to finally obtain a transparent fluorinated alkyl side-group acrylic resin.

[0009] The above method obtains a mixed solution by adding ethyl trifluoroacrylate and mixing within a certain ratio range, thereby causing the ethyl fluoroacrylate to undergo a polymerization reaction. In the process of forming the mixed solution, 90% of di-tert-butyl peroxide (DTBP) is first added as an initiator to carry out most of the reaction, and finally 10% of di-tert-butyl peroxide (DTBP) is added as an initiator to react, ensuring that a small amount of unreacted part after the first reaction is fully reacted again, thereby ensuring the adequacy of the reaction. Insulation is set to allow the mixed solution to react fully, and then vacuumization is performed to precipitate the solute of the mixed solution. Finally, drying is performed to obtain a transparent fluorinated alkyl side-group acrylic resin with high water resistance and aging resistance.

[0010] Furthermore, it also includes Step S6: 300 g of the fluorinated alkyl side group acrylic resin obtained in step S5, 60 g of dodecanedioic acid (DDDA), 1.2 g of benzoin and 3 g of a leveling agent were melted according to a weight ratio, and then a coating was prepared by electrostatic powder spraying; Step S7: The fluorinated alkyl side group acrylic resin obtained in step S5 is subjected to infrared testing, and then the coating obtained in step S6 is subjected to water contact angle testing, water absorption testing, and UVB aging testing.

[0011] The above settings can detect the performance of the coating through different tests.

[0012] Furthermore, the infrared test is as follows: The coating was scanned with an infrared thermal imager, and then the infrared spectrum was used to observe whether the bond energy of the OH bond, CH bond, C=O bond and CF bond in the fluorinated alkyl side group acrylic resin changed, so as to determine whether ethyl trifluoroacrylate underwent polymerization.

[0013] The above method can determine whether ethyl trifluoroacrylate undergoes polymerization reaction by analyzing whether different bond energies in fluorinated alkyl side group acrylic resin have changed, thereby obtaining whether ethyl trifluoroacrylate has undergone changes. If ethyl trifluoroacrylate has reacted, the trifluoro group has been decomposed to form CF bond energy.

[0014] Further, the water contact angle test is as follows: The proportion of ethyl trifluoroacrylate was changed according to the weight ratio to obtain coatings containing ethyl trifluoroacrylate in different proportions. The coatings were then tested using a contact angle meter to observe and compare the water contact angles of the coatings.

[0015] The above arrangement can determine whether the water resistance of the coating has changed by the water contact angle of the coating.

[0016] Further, the water absorption test comprises the following steps: (a1) Spray the coating onto the sample, then dry the sprayed sample, cool it at room temperature, weigh the cooled sample, and record the mass of the sample; (b1) Soak the sample weighed in step (a1) in water at a temperature within the range of 23±2°C for a period of time T, then take out the sample and wipe the surface of the sample with filter paper, then weigh the sample after the moisture is wiped off, and record the mass of the sample; (c1) Changing the proportion of ethyl trifluoroacrylate according to the weight ratio to obtain coatings containing ethyl trifluoroacrylate in different proportions, and then repeating steps (a1) to (b1) to test the water absorption rate of the coatings containing ethyl trifluoroacrylate in different proportions.

[0017] The above arrangement can obtain the water absorption rate corresponding to the coating containing different proportions of ethyl trifluoroacrylate, and then select the ethyl trifluoroacrylate proportion with the best water absorption rate.

[0018] Further, the UVB aging test comprises the following steps: (d1) performing a UVB aging test on the coating that does not contain ethyl trifluoroacrylate using a UV aging tester for 1000 h, and then obtaining a light retention rate curve of the coating that does not contain ethyl trifluoroacrylate; (e1) performing a UVB aging test on the coating in step S6 using a UV aging tester for 1000 h, and then obtaining a light retention rate curve of the coating containing ethyl trifluoroacrylate; (f1) Comparison of the gloss retention curve of the coating without ethyl trifluoroacrylate and the gloss retention curve of the coating with ethyl trifluoroacrylate.

[0019] The above settings can further reflect the gloss retention of the coating by detecting the anti-aging performance of the coating through comparative testing.

[0020] Furthermore, the polymerization temperature in step S2 is 135°C, and the preset temperature in step S5 is 145°C.

[0021] The above arrangement enables the polymerization reaction to proceed at the polymerization temperature, and then by presetting the temperature to 145° C., it is ensured that the polymerization reaction can proceed further after the temperature is raised to a certain level.

[0022] Furthermore, in step S5, maintaining the vacuum degree in the reactor within a preset pressure range specifically includes: maintaining the vacuum degree of the reactor within a range of 0.096-0.098 Mpa.

[0023] The above arrangement can ensure the vacuum degree of the reaction environment under this vacuum degree. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a flow chart of the working method of the present invention.

[0025] Figure 2 This is a mid-infrared test spectrum curve of the present invention.

[0026] Figure 3 This is a comparison diagram of water contact angles in the present invention.

[0027] Figure 4 It is the water absorption curve diagram in the present invention.

[0028] Figure 5 This is a light retention rate curve diagram of the present invention. DETAILED DESCRIPTION

[0029] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0030] Example 1.

[0031] The present invention provides a fluorinated alkyl side group acrylic resin for powder coatings. The following preparation materials are included: Ethyl trifluoroacrylate (TFEA), glycidyl methacrylate (GMA), methyl methacrylate (MMA), di-tert-butyl peroxide (DTBP), propylene glycol methyl ether acetate (PMA); The ratio of ethyl trifluoroacrylate (TFEA): glycidyl methacrylate (GMA): methyl methacrylate (MMA) ranges from 1~5:6~15:1~9.

[0032] Example 2.

[0033] In this embodiment, a fluorinated alkyl side group acrylic resin for powder coatings, The following preparation materials are included: Ethyl trifluoroacrylate (TFEA), glycidyl methacrylate (GMA), methyl methacrylate (MMA), di-tert-butyl peroxide (DTBP), propylene glycol methyl ether acetate (PMA); The ratio of ethyl trifluoroacrylate (TFEA): glycidyl methacrylate (GMA): methyl methacrylate (MMA) ranges from 1:6:1; The weight ratio of ethyl trifluoroacrylate (TFEA):di-tert-butyl peroxide (DTBP):propylene glycol methyl ether acetate (PMA) is in the range of 1:1.5:30.

[0034] Example 3.

[0035] In this embodiment, a fluorinated alkyl side group acrylic resin for powder coatings, The following preparation materials are included: Ethyl trifluoroacrylate (TFEA), glycidyl methacrylate (GMA), methyl methacrylate (MMA), di-tert-butyl peroxide (DTBP), propylene glycol methyl ether acetate (PMA); According to the weight ratio, ethyl trifluoroacrylate (TFEA): glycidyl methacrylate (GMA): methyl methacrylate (MMA) = 3:9:5, di-tert-butyl peroxide (DTBP) and propylene glycol methyl ether acetate (PMA) can be mixed in appropriate amounts according to the weight ratio; for example, the weight ratio of ethyl trifluoroacrylate (TFEA): di-tert-butyl peroxide (DTBP): propylene glycol methyl ether acetate (PMA) is 3:2.2:45.

[0036] Example 4.

[0037] In this embodiment, a fluorinated alkyl side group acrylic resin for powder coatings, The following preparation materials are included: Ethyl trifluoroacrylate (TFEA), glycidyl methacrylate (GMA), methyl methacrylate (MMA), di-tert-butyl peroxide (DTBP), propylene glycol methyl ether acetate (PMA); The ratio of ethyl trifluoroacrylate (TFEA): glycidyl methacrylate (GMA): methyl methacrylate (MMA) ranges from 5:15:9; The weight ratio of ethyl trifluoroacrylate (TFEA):di-tert-butyl peroxide (DTBP):propylene glycol methyl ether acetate (PMA) ranges from 5:2.5:50.

[0038] Example 5.

[0039] The specific steps of the preparation method of the fluorinated alkyl side group acrylic resin are as follows: S1 A stirrer, a constant pressure dropping funnel, a condenser, and a thermometer are installed on the reactor. In this embodiment, the reactor is a four-necked flask.

[0040] S2: adding propylene glycol methyl ether acetate (PMA) into the reactor, stirring it with a stirrer, and heating it to a polymerization temperature of 135°C after stirring; S3: ethyl trifluoroacrylate (TFEA): glycidyl methacrylate (GMA): methyl methacrylate (MMA) are uniformly mixed in a ratio of 3:9:5 within a ratio range of 1-5:6-15:1-9 according to a weight ratio, and then mixed with 90% of di-tert-butyl peroxide (DTBP) to obtain a mixed solution; S4: inject the mixed solution in step S3 into a constant pressure dropping funnel, and then drip it into the reactor at a uniform speed through the constant pressure dropping funnel. After the mixed solution is dripped, keep warm. After keeping warm for 2 hours, add the remaining 10% di-tert-butyl peroxide (DTBP) in step S3 into the reactor, and continue to keep warm for 2 hours to allow the mixed solution to react fully. S5 After the mixed solution has fully reacted, the temperature is continued to be raised to 145°C, and then the heating is stopped to keep the temperature, and the reactor is evacuated at the same time, so that the vacuum degree in the reactor is maintained within a preset pressure range of 0.096~0.098 Mpa. In this embodiment, the vacuum degree in the reactor is 0.097Mpa, so that the solvent of the mixed solution is removed, and then the precipitated material after the solvent is removed is placed in a vacuum drying oven and dried for 8-10 hours. In this embodiment, a transparent fluorinated alkyl side-group acrylic resin is obtained after drying for 9 hours.

[0041] S6 performs infrared tests on the fluorinated alkyl side group acrylic resins obtained in step S5. The infrared tests are as follows: The coating was scanned by an infrared thermal imager, and then the infrared spectrum was used to observe whether the bond energies of the OH bond, CH bond, C=O bond, and CF bond in the fluoroalkyl side group acrylic resin changed, such as Figure 2 As shown, 3440cm -1 The absorption peak of OH in ethyl trifluoroacrylate (TFEA) is 2953 cm -1 The absorption peak of CH in ethyl trifluoroacrylate (TFEA) is 1730 cm -1 The absorption peak of C=O in ethyl trifluoroacrylate (TFEA) is 1241 cm -1 The absorption peak at 910 cm is the absorption peak of the CF bond in ethyl trifluoroacrylate (TFEA). -1 847cm -1 These are the absorption peaks of -CH(O)CH- in glycidyl methacrylate (GMA). Since the trifluoro group of ethyl trifluoroacrylate (GMA) will form a fluoroalkyl side after the polymerization reaction, thus forming a CF bond, it can be judged that ethyl trifluoroacrylate (GMA) has undergone a polymerization reaction.

[0042] S7: 300 g of the fluorinated alkyl side group acrylic resin obtained in step S5, 60 g of dodecanedioic acid (DDDA), 1.2 g of benzoin and 3 g of a leveling agent are melted according to a weight ratio, and then a coating is prepared by electrostatic powder spraying.

[0043] Then, the coating obtained in step S6 is subjected to a water contact angle test, a water absorption test, and a UVB aging test.

[0044] The water contact angle test consists of the following steps: The coating obtained in step S6 and the coating without ethyl trifluoroacrylate (TFEA) were tested by a contact angle meter. The water drop volume was set to 2 μL. The sessile drop method was used for testing. The coating was tested at 5 different locations, and then the water contact angles of the coatings were compared. Figure 3 As shown, the water contact angle of the coating without ethyl trifluoroacrylate (TFEA) is 75.2°, and the water contact angle when the ethyl trifluoroacrylate (TFEA) ratio is 3 is 103.5°. It can be concluded that the water contact angle of the coating containing ethyl trifluoroacrylate (TFEA) is larger, thereby making the coating more hydrophobic. The improvement of the hydrophobicity of the coating is conducive to hindering the penetration of external water molecules into the coating, thereby increasing the water resistance of the coating; then the ratio of ethyl trifluoroacrylate is changed according to the weight ratio. In this embodiment, glycidyl methacrylate (GMA) and methyl methacrylate (MMA) are mixed with ethyl trifluoroacrylate (TFEA) in a ratio of 2, ethyl trifluoroacrylate (TFEA) in a ratio of 4, and ethyl trifluoroacrylate (TFEA) in a ratio of 5 in a ratio of 9:5, and then steps S5~ are repeated. S6, and then obtain coatings containing different proportions of ethyl trifluoroacrylate (TFEA), and finally test the coatings using a contact angle meter. By comparing the water contact angles of different coatings, it can be concluded that the larger the proportion of ethyl trifluoroacrylate (TFEA), the larger the water contact angle of the coating.

[0045] The water absorption test consists of the following steps: (a1) Spray the coating onto the sample, then dry the sprayed sample, cool it at room temperature, weigh the cooled sample, and record the sample mass m; (b1) Soak the sample weighed in step (a1) in water at a temperature within the range of 23±2°C for a period of time T, then take out the sample and wipe the surface of the sample with filter paper, then weigh the sample after the moisture is wiped off, and record the mass M of the sample; (c1) Calculate the water absorption W of the coating as follows: ; The proportion of ethyl trifluoroacrylate (TFEA) was changed according to the weight ratio within the proportion range of 1 to 5, and then steps (a1) to (b1) were repeated to test the water absorption rate of the coating containing different proportions of ethyl trifluoroacrylate, such as Figure 4As shown, the water absorption curve of the coating containing different proportions of ethyl trifluoroacrylate is obtained. From the analysis of the water absorption curve, it is found that with the increase of the proportion of ethyl trifluoroacrylate (TFEA), the water absorption of the coating gradually decreases. When the proportion of ethyl trifluoroacrylate (TFEA) is 30, the water absorption of the coating rapidly decreases to about 5%. When the proportion of ethyl trifluoroacrylate (TFEA) is 35, the water absorption of the coating tends to be flat. This is because the trifluoro group of ethyl trifluoroacrylate (TFEA) introduces a hydrophobic fluoroalkyl side group into the acrylic resin molecular chain, which reduces the hydrophilicity of the coating and makes it difficult for external water molecules to penetrate into the interior of the coating, thereby improving the water resistance of the coating.

[0046] UVB aging testing includes the following steps: (d1) The coating without ethyl trifluoroacrylate (TFEA) is subjected to a UVB aging test by using a UV aging tester, the test time is 1000 h, and then the light retention rate curve of the coating without ethyl trifluoroacrylate (TFEA) is obtained; (e1) performing a UVB aging test on the coating in step S6 using a UV aging tester for 1000 h, and then obtaining a light retention rate curve of the coating containing ethyl trifluoroacrylate (TFEA); (f1) Figure 5 As shown, the curve with a white black frame represents the light retention curve of the coating containing ethyl trifluoroacrylate (TFEA), and the curve with a black frame represents the light retention curve of the coating without ethyl trifluoroacrylate (TFEA). By comparing the light retention curve of the coating without ethyl trifluoroacrylate (TFEA) and the light retention curve of the coating containing ethyl trifluoroacrylate (TFEA), it can be concluded that when UVB aging reaches 1000h, the light retention rate of the coating containing ethyl trifluoroacrylate (TFEA) remains at about 96%, which is significantly higher than the light retention rate of the coating without ethyl trifluoroacrylate (TFEA). This is because the CF bond in ethyl trifluoroacrylate (TFEA) has extremely high bond energy and is not easily destroyed by the outside world, thereby improving the overall anti-aging performance of the coating; while the light retention rate of the coating containing ethyl trifluoroacrylate (TFEA) exceeds 100% in the early stage of UVB aging, because the resin of the coating will soften when heated, and the proportion of resin on the coating surface increases.

[0047] The fluorinated alkyl side-group acrylic resin after infrared testing, water contact angle testing, water absorption testing and UVB aging testing can further verify that the fluorinated alkyl side-group acrylic resin and the coating finally formed using the resin can effectively improve the water resistance and gloss retention of the powder coating.

Claims

1. A fluorinated alkyl side group acrylic resin for powder coatings, characterized in that: The following preparation materials are included: Ethyl trifluoroacrylate (TFEA), glycidyl methacrylate (GMA), methyl methacrylate (MMA), di-tert-butyl peroxide (DTBP), propylene glycol methyl ether acetate (PMA); The weight ratio of ethyl trifluoroacrylate (TFEA): glycidyl methacrylate (GMA): methyl methacrylate (MMA) is in the range of 1~5:6~15:1~9; The weight ratio of ethyl trifluoroacrylate (TFEA): di-tert-butyl peroxide (DTBP): propylene glycol methyl ether acetate (PMA) is in the range of 1-5: 1.5-2.5: 30-50.

2. The method for preparing a fluorinated alkyl side group acrylic resin for powder coating according to claim 1, characterized in that: The following steps are involved: S1: A stirrer, a constant pressure dropping funnel, a condenser and a thermometer are installed on the reactor; S2: adding propylene glycol methyl ether acetate (PMA) into the reactor, stirring the reactor with a stirrer, and heating the reactor to a polymerization temperature after stirring. S3: uniformly mixing ethyl trifluoroacrylate (TFEA), glycidyl methacrylate (GMA) and methyl methacrylate (MMA) in a weight ratio of 1-5:6-15:1-9, and then mixing with 90% of di-tert-butyl peroxide (DTBP) to obtain a mixed solution; S4: injecting the mixed solution in step S3 into a constant pressure dropping funnel, and then dripping it into the reactor at a uniform speed through the constant pressure dropping funnel. After the mixed solution is dripped, it is kept warm for a period of time T. After that, the remaining 10% of di-tert-butyl peroxide (DTBP) in step S3 is added to the reactor, and the temperature is kept warm for a period of time T. S5 After the mixed solution has fully reacted, continue to heat and raise the temperature to a preset temperature, then stop heating and keep warm, and at the same time evacuate the reactor to maintain the vacuum degree in the reactor within a preset pressure range to remove the solvent, then put the precipitated material after the solvent is removed into a vacuum drying oven and dry for 8-10 hours to finally obtain a transparent fluorinated alkyl side-group acrylic resin.

3. The method for preparing a fluorinated alkyl side group acrylic resin for powder coating according to claim 1, characterized in that: Also includes Step S6: 300 g of the fluorinated alkyl side group acrylic resin obtained in step S5, 60 g of dodecanedioic acid (DDDA), 1.2 g of benzoin and 3 g of a leveling agent were melted according to a weight ratio, and then a coating was prepared by electrostatic powder spraying; Step S7: The fluorinated alkyl side group acrylic resin obtained in step S5 is subjected to infrared testing, and then the coating obtained in step S6 is subjected to water contact angle testing, water absorption testing, and UVB aging testing.

4. The method for preparing a fluorinated alkyl side group acrylic resin for powder coating according to claim 3, characterized in that: The infrared test is as follows: The coating was scanned with an infrared thermal imager, and then the infrared spectrum was used to observe whether the bond energy of the OH bond, CH bond, C=O bond and CF bond in the fluorinated alkyl side group acrylic resin changed, so as to determine whether ethyl trifluoroacrylate underwent polymerization.

5. The method for preparing a fluorinated alkyl side group acrylic resin for powder coating according to claim 3, characterized in that: The water contact angle test is as follows: The proportion of ethyl trifluoroacrylate was changed according to the weight ratio to obtain coatings containing ethyl trifluoroacrylate in different proportions. The coatings were then tested using a contact angle meter to observe and compare the water contact angles of the coatings.

6. The method for preparing a fluorinated alkyl side group acrylic resin for powder coatings according to claim 3, characterized in that: The water absorption test comprises the following steps: (a1) Spray the coating onto the sample, then dry the sprayed sample, cool it at room temperature, weigh the cooled sample, and record the mass of the sample; (b1) Soak the sample weighed in step (a1) in water at a temperature within the range of 23±2°C for a period of time T, then take out the sample and wipe the surface of the sample with filter paper, then weigh the sample after the moisture is wiped off, and record the mass of the sample; (c1) Changing the proportion of ethyl trifluoroacrylate according to the weight ratio to obtain coatings containing ethyl trifluoroacrylate in different proportions, and then repeating steps (a1) to (b1) to test the water absorption rate of the coatings containing ethyl trifluoroacrylate in different proportions.

7. The method for preparing a fluorinated alkyl side group acrylic resin for powder coatings according to claim 3, characterized in that: The UVB aging test comprises the following steps: (d1) performing a UVB aging test on the coating that does not contain ethyl trifluoroacrylate using a UV aging tester for 1000 h, and then obtaining a light retention rate curve of the coating that does not contain ethyl trifluoroacrylate; (e1) performing a UVB aging test on the coating in step S6 using a UV aging tester for 1000 h, and then obtaining a light retention rate curve of the coating containing ethyl trifluoroacrylate; (f1) Comparison of the gloss retention curve of the coating without ethyl trifluoroacrylate and the gloss retention curve of the coating with ethyl trifluoroacrylate.

8. The method for preparing a fluorinated alkyl side group acrylic resin for powder coatings according to claim 3, characterized in that: The polymerization temperature in step S2 is 135°C, and the preset temperature in step S5 is 145°C.

9. The method for preparing a fluorinated alkyl side group acrylic resin for powder coatings according to claim 3, characterized in that: Maintaining the vacuum degree in the reactor within a preset pressure range in step S5 specifically includes: maintaining the vacuum degree of the reactor within a range of 0.096-0.098 Mpa.

Citation Information

Patent Citations

  • Organic silicon resin for powder coating as well as preparation method and application of organic silicon resin

    CN117624615A